Supplement to Frege's Theorem and Foundations for Arithmetic

Derivation of the Principle of Extensionality from Basic Law V

[Note: We use \(\epsilon F\) to denote the extension of the concept \(F\).]

Assume Extension(x) and Extension(y). Then \(\exists F(x\eqclose \epsilon F)\) and \(\exists G(y\eqclose \epsilon G)\). Let \(P,Q\) be arbitrary such concepts; i.e., suppose \(x\eqclose \epsilon P\) and \(y \eqclose \epsilon Q\).

Now to complete the proof, assume \(\forall z(z\in x \equiv z\in y)\). It then follows that \(\forall z(z\in\epsilon P\equiv z\in\epsilon Q)\). So, by the Law of Extensions and the principles of predicate logic, we may convert both conditions in the universalized biconditional to establish that \(\forall z(Pz\equiv Qz)\). So by Basic Law V, \(\epsilon P =\epsilon Q\). So \(x = y\).

Copyright © 2017 by
Edward N. Zalta <>

This is a file in the archives of the Stanford Encyclopedia of Philosophy.
Please note that some links may no longer be functional.
[an error occurred while processing the directive]